Problematyka administracji publicznej na łamach „Gazety Administracji i Policji Państwowej” z 1923 roku - Przygodzki, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article is devoted to the problems of public administration which were present in Gazeta Administracji i Policji Państwowej in the year 1923. The choice of the 5th annual volume of 1923 was not accidental as there have been three changes in ruling cabinet of General W. Sikorski, W. Witos and W. Grabski in that year. Each of them had ambitious plans to unify and streamline Polish administration. It was in that year when the Commission for Administrative Reform was established, which extensively dealt with administration matters and prepared guidelines for the introduction of a uniform system for the whole country’s self-government bodies, at all levels of territorial division of the country, in accordance with the principles of the March Constitution. The fall of the committee, together with the resignation of Sikorski’s government, did not thwart its work, and another cabinet of “Chjeno-Piast” coalition, based on the findings of its predecessors, prepared a draft of self-government acts and sent them to the Parliament, but without a draft concerning the provinces. We could read about all these facts on the pages of Gazeta Administracji i Policji Państwowej, which reliably informed of any changes in governments, presenting the profiles of prime ministers together with their political programs, as well as profiles of interior ministers and most important officials of the ministry, responsible for the shape of changes in public administration.
Keywords: Druga Rzeczpospolita; administracja publiczna; Polska (1918-1939); samorząd